Tribological behavior and self-repairing performance of chromium oxide films over multiple thermal cycles from 25 °C to 1000 °C. (January 2022) - Liao, Mengde; Xu, Wenju; Liu, Xiaohong; Jia, Bingsen; Sun, Chufeng; Li, Hongxuan
Abstract: Chromium oxide film was prepared on the surface of Inconel 718 alloy by multi-arc ion plating; and the as-deposited film was annealed at elevated temperatures of 960 °C, 980 °C, and 1000 °C. The as-deposited and annealed films were characterized by scanning electron microscopy-energy dispersive spectrometry, high-resolution transmission electron microscopy, and X-ray diffraction. Their mechanical properties were determined with a nanomechanical testing system and a scratch tester, and their friction and wear behavior at ambient temperature and elevated temperatures of up to 1000 °C was evaluated in relation to the formation of the network-like surface bulge structure. It was found that high-temperature annealing treatment of the as-deposited chromium oxide film generates a unique surface bulge structure, which is due to the segregation and oxidation of the elements in the substrate alloy towards the grain boundaries thereat. The bulge structure transforms the plane contact mode of the annealed films sliding against alumina ball in a ball-on-disk configuration to a point contact mode, which is beneficial for reducing the friction coefficient and wear rate of the annealed films over multiple thermal cycles. Moreover, the bulge structure damaged during sliding can be regenerated and replenished by secondary annealing, which provides the chromium oxide film with self-repairing ability upon high temperature sliding. The present approach could help to shed light on the development of novel high-performance chromium oxide films with continuous lubricity from room temperature to elevated temperatures of over 1000 °C. Highlights: The alloy elements oxidize to form a convex structure after annealing. The network convex structure changes the friction state of the films. The film with network convex structure has low friction coefficient. The film with convex structure has self-repairing ability by annealing.